Integrated metabolomic and transcriptomic analysis reveals digestive tract adaptations to high altitude in Bayanbulak sheep - Chen, Xuhui; Chen, Bin; Yang, Yaling; Liu, Lingling; Liu, Wujun (Frontiers in Veterinary Science, 2025)
IntroductionHigh-altitude adaptation in Bayanbulak sheep may modulate digestive tract functions. This study investigated differences in digestive tract metabolites between Bayanbulak sheep at high altitude (2,400–4,400 m) and Turpan black sheep at low altitude (−154 m). We performed untargeted metabolomics analysis on ruminal fluid, small intestinal contents, and fecal metabolites, measured serum biochemical parameters, and examined skin tissue morphology. Differential gene expression in ruminal fluid was analyzed using RNA-seq. Key findings include: (1) Bayanbulak sheep showed significantly higher including total antioxidant capacity (TAC), superoxide dismutase (SOD), catalase (CAT), interferon-γ (IFN-γ), interleukin-2 (IL-2), total cholesterol, glucose, and triglyceride levels compared to Turpan black sheep (p < 0.05); (2) Epidermal thickening was observed in Bayanbulak sheep under high-altitude conditions. (3) Significant upregulation of metabolites including spermidine, 5′-adenylic acid (AMP), oleic acid (OA), and nicotine occurred in Bayanbulak sheep, accompanied by enhanced activity in glutathione metabolism, AMP-activated protein kinase (AMPK) signaling pathway, purine metabolism, and thermogenesis pathways. (4) Co-detected metabolites - vanillin, pinacidil, and 4-hydroxychalcone (4-HC) - exhibited significant differential abundance across rumen, small intestine, and feces in Bayanbulak sheep, with concurrent upregulation of associated metabolic pathways. (5) In the rumen of Bayanbulak sheep, genes CPT1B (carnitine palmitoyltransferase 1B), CPT1C (carnitine palmitoyltransferase 1C), and CASTOR2 (cytosolic aspartate tRNA-specific ribozyme) were significantly upregulated (p < 0.05), collectively enriched in the AMPK signaling pathway and mTOR signaling pathway, while the small intestinal gene TM4SF18 (transmembrane 4 L six family member 18) was significantly downregulated (p < 0.01), co-enriched in the ferroptosis pathway.ConclusionBayanbulak sheep adapt to high-altitude hypoxia and thermal stress through epidermal thickening and synergistic interactions between blood and digestive tract metabolites. These adjustments enhance antioxidant capacity, energy reserves, and immune function, offering a robust model for high-altitude adaptation.